Time Course of Inflammatory and Endocrine Factors Following a Single-Bout of High-Intensity WB-EMS – A Randomized Crossover Study - Teschler, Marc; Bothur, Evita; Samel, Nadine; Waranski, Melina; Walscheid, Rüdiger; Schmitz, Boris; Mooren, Frank C. (Research quarterly for exercise and sport, 2025)
The aim of the study was to gain insight into the time course of whole-body electromyostimulation (WB-EMS)-induced inflammatory and endocrine factors over 72 h. Twelve healthy individuals (5 men, 7 women; 33.0 ± 12 years) randomly performed a single 20-minute high-intensity WB-EMS and a time- and intensity-matched whole-body circuit training (CT) with a 3-week wash-out period. Blood samples were taken pre- and post-training and at 1.5, 3, 24, 48 and 72 h after exercise to assess creatine kinase (CK), myoglobin, and creatinine, cell populations (red and white blood cells [RBC, WBC], thrombocytes), cytokines (interleukin IL-1Ra, IL-6, IL-10, monocyte chemoattractant protein 1 [MCP-1]), angiogenic factors (IL-8, vascular endothelial growth factor [VEGF], thrombospondin), adipokines (leptin, adiponectin), and hormones (testosterone, cortisol). WB-EMS induced significant CK elevations peaking at 72 h (WB-EMS, 18,358 ± 21,380 vs. CT, 186 ± 129 U/l; time × group, p < .001) and increased MCP-1 after 3 h (time × group, p < .05). Both protocols induced similar effects on WBC, RBC, IL-1Ra, IL-8, leptin, and cortisol (overall time effect, all p < .01). WBC increased at 1.5 and 3 h (p < .001) and RBC decreased over 72 h (p < .05). IL-1Ra peaked at 1.5 h (p < .01) and IL-8 was elevated at 3–72 h (p < .05). The cortisol and leptin decreases lasted up to 48 and 72 h, respectively (p < .05). Despite inducing muscle damage, a single of high-intensity WB-EMS session did not lead to significantly different inflammatory and hormonal signaling compared to an acute aerobic CT session. Prolonged studies are needed to investigate whether regular WB-EMS leads to more pronounced training adaptations despite similar signaling signatures.